PENGARUH PEMBERIAN Trichoderma Sp UNTUK MENGENDALIKAN PENYAKIT LAYU FUSARIUM PADA BEBERAPA JENIS PISANG DI LAHAN YANG TELAH TERINFEKSI - BUKHARI BUKHARI; NURYULSEN SAFRIDAR (Universitas Lancang Kuning, 2018)
The experimental design used was a 4x4 factorial with 2 replications in a randomized block design (RAK) pattern. The first factor is the Type of Banana (J) consisting of 4 levels: J1 (Raja Banana ), J2 (Ambon Banana), J3 (Barangan Banana) and J4 (Geupok Banana). The second factor was the mixing of Trichoderma Sp with organic manure aplication (D) consisting of 4 levels: D0 (without trichoderma sp), D1 (200 g trichoderma sp in 4 kg manure), D2 (200 gr trichoderma sp in 8 kg manure), and D3 (200 gr trichoderma sp in 12 kg manure). Observations made include: Intensity of Fusarium oxysporum wilting attack, number of leaves, Leaf length and stem diameeter. The results showed that the type of banana had a very significant effect on the intensity of fusarium oxysporum wilt disease and the number of leaves, but no significant effect on the length and diameter of the stem. Barangan Bananas and Ambon Bananas show stronger resilience (more resistant to fusarium oxysporum wilt disease). While the Raja Banana and Geupok Bananas look more sensitive to the attack of the disease. The mixing of Trichoderma Sp with organic manure also significantly influenced the intensity of fusarium oxysporum wilt disease, number of banana leaf and leaf length, but no significant effect on stem diameter. The best dose is found in treatment D1, but not different from D2. An increase in the amount of organic matter manure